Pengaruh wajib pajak badan, kepatuhan wajib pajak badan, dan pemeriksaan pajak terhadap penerimaan Pajak Penghasilan badan pasal 25/29 pada Kantor Pelayanan Pajak Pratama Tampan Pekanbaru - Erni Susanti; Zirman '; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine the influence of corporate taxpayers, compliance of corporate taxpayer, and tax audit the on corporate income tax article 25/29 at tax office (KPP) Pratama Tampan Pekanbaru for the period of 2009 until 2013. Population in this research is all active corporate taxpayers at office (KPP) Pratama Tampan Pekanbaru for the period of 2009 until 2013. Data are collected with research of field, bibliography, and documentation. Regression models used has met the assumption of classical test. This research used multiple linear regression analysis technique. Based on the results of analysis show that corporate taxpayers, compliance of corporate taxpayer and tax audit have a significantly influence on corporate income tax article 25/29 at tax office (KPP) Pratama Tampan Pekanbaru.Keywords : Corporate taxpayers, compliance of corporate taxpayer, tax audit, corporate income tax.